Dinamika Komunikasi Anak dalam Keluarga Pasca Perselingkuhan Orang Tua di Kabupaten Subang - Ainun Putri Wahyuni; Safutra Rantona; Yasundari Yasundari; Melly Maulin Purwaningwulan (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study aims to understand the dynamics of children’s communication within families after parental infidelity in Subang Regency, with a focus on conflict, problem-solving strategies, and conformity. The research employed a qualitative approach using a case study method, with data collected through purposive sampling involving four key informants and five supporting informants. The findings indicate that post-affair conflicts often lead to children’s withdrawal from family interactions, while problem-solving efforts are not always successful in restoring trust and repairing family relationships due to unresolved emotional wounds. Children’s conformity tends to become increasingly closed and restrictive, with the family no longer functioning as a safe space to express feelings and share concerns. Parental infidelity significantly disrupts family communication, particularly in parent–child interactions, as children tend to feel insecure, lose trust, and adopt rigid or defensive communication patterns. This condition reflects a broader psychological impact in which children experience emotional distress, confusion, and difficulties in establishing meaningful relationships. Moreover, the study highlights that unresolved family communication breakdowns may contribute to long-term consequences, such as reduced self-esteem and heightened vulnerability to stress. The research underscores the importance of maintaining open, honest, and empathetic communication to support children’s emotional recovery after parental infidelity. It also recommends seeking professional assistance, such as counselors or psychologists, when families are unable to independently rebuild healthy communication patterns. This provides not only emotional relief but also preventive measures for further deterioration of family relationships.